Role of Chrysophanol in Epithelial-Mesenchymal Transition in Oral Cancer Cell Lines via a Wnt-3-Dependent Pathway. (15th September 2020) - Chung, Ping-Chen; Hsieh, Po-Chun; Lan, Chou-Chin; Hsu, Po-Chih; Sung, Min-Yi; Lin, Ya-Hsuan; Tzeng, I.-Shiang; Chiu, Valeria; Cheng, Ching-Feng; Kuo, Chan-Yen
Abstract : Oral cancer belongs to the group of head and neck cancers. If not diagnosed or treated early, it can be life threatening. Epithelial-mesenchymal transition (EMT) plays an important role in tumor formation and progression. An increase in the presence of the EMT phenotype causes tumor cell proliferation, migration, invasion, and poor prognosis. Therefore, attenuating carcinogenesis via EMT inhibition is a good strategy. Herein, we will determine the pharmacological effects of chrysophanol on the EMT in FaDu cells. To analyze EMT, we detected the expression EMT markers, including α -SMA, β -catenin, vimentin, N-cadherin, E-cadherin, phospho-GSK-3 β, and nuclear translocations of p65 and β -catenin by western blotting. Additionally, accumulating evidence indicates that reactive oxygen species (ROS) mediate EMT. Our results showed that the level of ROS was significantly increased after chrysophanol treatment. We further speculated that chrysophanol-mediated EMT and metastasis are involved in the Wnt-3-dependent signaling pathway. The inhibition of the EMT phenotype and metastasis and accumulation of ROS caused by chrysophanol was reversed by treatment with the Wnt-3 agonist Bml 284. Therefore, our findings indicated that chrysophanol altered EMT formation, ROS accumulation, and metastasis via the Wnt-3-dependent signaling pathway.